Geographic Location as a Determining Factor In The Purchase Of Dairy Products During The Covid-19 Pandemic (Revista Espaço e Geografia, 2022)
Dietary patterns can vary in the Brazilian geographic regions, which have been affected differently by the COVID-19 pandemic. This study aimed to determine whether the place of residence of the individuals affected the consumption of dairy products during the pandemic, considering both the amount of product consumed and the factors that influence the purchase decision. Adjusted Pearson residuals were used to evaluate the association between the variable state and those related to the consumption of dairy products. Data collection was performed using an online questionnaire application, from April 23 to May 3, 2020. The results showed that, for most dairy products, a significant association was observed between the place of residence and the consumption of dairy products. A greater association with the maintenance or higher consumption was observed for the regions with a higher intake of dairy products, and the brand that consumers were used to buy was the determining factor at the time of purchase, even in the face of a financial crisis. It was also possible to determine the states that were most aware of the actions of companies during the pandemic and the importance of good nutrition in a public health crisis. Finally, the results can contribute to a better understanding of the particularities of the consumption of dairy products in Brazil, besides assessing the consumers’ behavior in the current economic crisis.